2011
DOI: 10.17221/313/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Compositional characteristics and nutritional quality of Eurasian beaver (Castor fiber) meat

Abstract: The meat of Eurasian beaver (Castor fiber) as obtained in Lithuania contained 21.4% crude protein with high amounts of glutamic acid (152.6 mg/g), aspartic acid (87.6 mg/g), lysine (81.8 mg/g), leucine (75.7 mg/g), arginine (60.4 mg/g), and isoleucine (60.1 mg/g). This meat could be a high quality protein source because of its well-balanced essential amino acid composition. Polyunsaturated fatty acids were predominant with a percentage of 41.58% in thighs and of 42.12% in the fat depot of tails. Hexadecanoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
15
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 27 publications
(30 reference statements)
10
15
2
Order By: Relevance
“…Contrary, Korzeniowski et al [33] found higher values (22.09 and 1.33 g 100 g −1 ) for meat (as an average of the three elements: thigh, loin and tail) from farmed beavers aged between 7 and 19 years. Similar content of protein and ash to present results was also stated by Razmaitė et al [12] in thigh of wild beavers hunted in Lithuania (21.6 and 1.09%), and Strazdina et al [34] for biceps femoris (21.39 and 1.13%) and longissimus lumborum (21.81 and 1.20%) from Latvian animals. The stated differences in literature could be connected with different time of hunting or different condition of beaver's habitat in mentioned countries of Central Europe.…”
Section: Proximate Compositionsupporting
confidence: 91%
See 4 more Smart Citations
“…Contrary, Korzeniowski et al [33] found higher values (22.09 and 1.33 g 100 g −1 ) for meat (as an average of the three elements: thigh, loin and tail) from farmed beavers aged between 7 and 19 years. Similar content of protein and ash to present results was also stated by Razmaitė et al [12] in thigh of wild beavers hunted in Lithuania (21.6 and 1.09%), and Strazdina et al [34] for biceps femoris (21.39 and 1.13%) and longissimus lumborum (21.81 and 1.20%) from Latvian animals. The stated differences in literature could be connected with different time of hunting or different condition of beaver's habitat in mentioned countries of Central Europe.…”
Section: Proximate Compositionsupporting
confidence: 91%
“…The fat content in present study was higher compared to Lithuanian research (0.51%) [12], but considerably lower than Latvian (3.63-4.29%) [34,36], and Polish (3.8-5.1%) [5,15,35] investigations included sexually mature wild beavers. The highest fat content (5.80 g 100 g −1 ) reported Korzeniowski et al [33] for meat from farmed beavers aged between 7 and 19 years and weighing between 15.5 and 20.8 kg.…”
Section: Proximate Compositioncontrasting
confidence: 69%
See 3 more Smart Citations